Identification of Vortex Cores in Cerebral Aneurysms on 4D Flow MRI - Futami, K.; Uno, T.; Misaki, K.; Tamai, S.; Nambu, I.; Uchiyama, N.; Nakada, M. (American Journal of Neuroradiology, 2019)
BACKGROUND AND PURPOSE: The complexity and instability of the vortex flow in aneurysms are factors related to the rupture risk of unruptured cerebral aneurysms. We identified aneurysm vortex cores on 4D flow MR imaging and examined the relationship of these factors with the characteristics of cerebral aneurysms.MATERIALS AND METHODS: We subjected 40 aneurysms (37 unruptured, 3 ruptured) to 4D flow MR imaging. We visualized streamlines with velocities below the threshold—that is, a percentage value of the aneurysm maximum inflow velocity—and progressively decreased the threshold to identify vortex cores as thin, streamline bundles with minimum velocities. Complexity and stability were compared in aneurysms with a smooth surface and those with blebs or daughter sacs.RESULTS: The threshold for visualizing vortex cores ranged from 3% to 13% of the maximum inflow velocity. Vortex cores could be visualized in 38 aneurysms; in 2, they were not visualized through the cardiac cycle. A simple flow pattern (single vortex core) was identified in 27 aneurysms; the other 13 exhibited a complex flow pattern. The cores were stable in 32 and unstable in 8 aneurysms. Significantly more aneurysms with-than-without blebs or daughter sacs had a complex flow pattern (P = .006). Of the 3 ruptured aneurysms, 1 aneurysm had an unstable vortex core; in the other 2, the vortex core was not visualized.CONCLUSIONS: The identification of vortex cores on 4D flow MR imaging may help to stratify the rupture risk of unruptured cerebral aneurysms.CFDcomputational fluid dynamics